LEVELS OF HUMAN RESOURCE MANAGEMENT SKILLS IN RECREATIONAL AND SPORTS ORGANIZATIONS - Tolchieva, Hanna; Saienko, Volodymyr (Public Management and Policy, 2026)
The article examines the current problems of effective human resource management in the context of dynamic changes in the organizational environment and increased competition in the field of recreational and sports activities. Today's organizations will require systematic assessment tools that will allow them to quickly identify problematic aspects of their operations, determine the effectiveness of management decisions, and formulate changes in their thinking for advancement. efficiency of activity. The purpose of the article is to scientifically substantiate the levels of human resource management skills in recreational and sports organizations as a factor in coordinating the organization's strategic goals, making effective decisions, and gaining a competitive advantage. The article examines the important analysis and assessment of processes that are carried out in organizations, as an important tool for increasing the effectiveness of management and identifying institutional weaknesses, which will require creative actions. The scientific approaches to the assessment of human resource management are emphasized and the specificity of the application of various methods, techniques and indicators to management is highlighted in relation to the specifics of the organization’s activities. Recreational-sports directness. To achieve the goals set, a complex of scientific methods of investigation, close analysis, identification, leveling and systematization of theoretical provisions is used to evaluate management processes and the effectiveness of human resource management. This made it possible to identify key approaches to the formation of a system of evaluation indicators and name officials who influence the effectiveness of management activities. The work is committed to the importance and development of senior human resource management skills as a means of achieving the strategic goals of the organization, increasing the quality of management decisions and shaping competitive superior It has been established that the systematic application of current methods of analysis and assessment of personnel management facilitates the identification of weaknesses in the activities of the organization, the improvement of management mechanisms and promotion the effectiveness of the functioning of the organization of the recreational and sports sphere.